The Investigation of Fire Effects to Structural Elements of a Mobile Unit with a Compact Nuclear Power Plant - O. A. Gubeladze; A. R. Gubeladze (Глобальная ядерная безопасность, 2022)
During the first twenty years of the ХХI century a number of a different nature armed conflicts have occurred. In some of them states with nuclear-missile take part. The article researches one of the phases of emergency situation growth driven by fire generated conventional weapon on the mobile launch platform with solid-propellant ballistic missile. The simulation of the thermal effect on air frame and transporter-launcher container is performed, the result calculation valuation and experiment are carried out.